TUTUR WIDHI SASTRA DHARMA KAPATIAN: ANALISIS STRUKTUR DAN FUNGSI - Putu Ardiyanti, Gusti Ayu; Rai Putra, Ida Bagus (Humanis, 2017)
Abstract This through survey is about Tutur Widhi Sastra Dharma Kapatian. The aim of this survey is able to describe the structure and the function that is stated in Tutur Widhi Sastra Dharma Kapatian. Based on the theory that is used to focus on theory from Teeuw. For analysis function based on the structure of the theory that is presented by Teeuw and Ratna. The Methode that is used to prepare the data namely, observation method and read that supported of making note and translation technique and presentationof analysis data used informal method. The production is able to get in this survey for talking the language element, language value, Widhi Sastra Dharma Kapatian, Tutur Yama Purwana Tattwa, Tutur Uma Tattwa, Tata Cara Maprateka Rare, Panca Sudha Atma, Pawarah Sang Hyang Yama, ceremony activities,  tools of activities, and the sound of the God that build Tutur Widhi Sastra Dharma Kapatian as the structure of elements. All of this elements has a relationship one each other, and it is not separated with the function for the Bali human life such as phylosofy, field, education and sosioly.